Design recommendations for XR-based motor rehabilitation exergames at home - Lorenz, Emanuel A.; Bråten Støen, Andreas; Lie Fridheim, Magnus; Alsos, Ole Andreas (Frontiers in Virtual Reality, 2024)
Acquired brain injuries pose significant societal and individual challenges worldwide. The adoption of XR technologies presents an opportunity to enhance current rehabilitation procedures. However, a comprehensive understanding of the specific requirements of different user groups in XR-based rehabilitation remains incomplete. Our objective was to identify design recommendations for designers and researchers of XR-based exergames for motor rehabilitation for lower-limb motor recovery at home. We used a human-centered design process, interviewing central stakeholders to understand their perspectives and using thematic analysis to identify recurring themes and insights related to XR-based rehabilitation. The resulting themes for integrating XR-based exergames into ABI rehabilitation were safety, flexibility, efficacy, usability, technology, motivation, ownership, and social factors. By addressing technical and user-oriented demands, our resulting design recommendations aid designers in developing meaningful XR-based rehabilitation exercises.